The Role of Knowledge Management in Enhancing Organizational Performance: A Comprehensive Review - Thomas H. Sihombing; Miska Irani Br Tarigan; Darna Sitanggang; Theresa Sisilia Situmorang (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This research aims to analyze the role of knowledge management in improving organizational performance. This research uses a qualitative method with a literature review approach, examining various national and international scientific journals published between 2019 and 2025. Data was obtained thru documentation techniques from secondary sources such as Google Scholar, ResearchGate, ScienceDirect, and SpringerLink. Analysis was conducted using content analysis and thematic synthesis methods to identify patterns of relationships between knowledge management dimensions and organizational performance. The research results indicate that effective knowledge management implementation has a positive impact on improving organizational performance, both in terms of operational efficiency, innovation, and competitive advantage. The four main dimensions of knowledge management that play the most significant role are knowledge creation, knowledge storage, knowledge sharing, and knowledge application. Additionally, organizational culture, transformational leadership, and employe commitment are key supporting factors for the successful implementation of knowledge management. Thus, it can be concluded that the systematic and integrated management of knowledge is an important foundation for organizations to achieve superior and sustainable performance in the digital age.